Should We Diagnose Psychopathology in Infancy?. Issue 3 (May 2015) - Onnembo, Jessica; Beal, Judy A.
Abstract : Diagnosing psychopathology in very young children is an emerging debate in newborn and pediatric clinical practice. Potential advantages and disadvantages are discussed.